Problems and challenges in providing feedback to clinical teachers on their educational performance: A mixed-methods study - Sepideh Jamshidian; Nikoo Yamani; Mohammad Reza Sabri; Fariba Haghani (Wolters Kluwer Medknow Publications, 2019)
INTRODUCTION: Given the importance of feedback to improve teachers' educational performance, the current study aimed to identify the challenges and problems involved in providing feedback to clinical teachers on their educational performance. MATERIALS AND METHODS: In the first phase of this mixed-methods study, the clinical teachers, students, and university officials were interviewed on feedback problems and challenges. After an inductive content analysis, and based on the problems enlisted, a ten-item questionnaire was developed. Subsequently, 25 clinical teachers completed the questionnaire by scoring the importance and urgency of each problem. RESULTS: Overall, 18 individual and group interviews were conducted with 24 people. A total of ten themes and five categories emerged, including "lack of transparency of feedback system," "absence of criticizability culture," "lack of motivation to improve performance," "failure to consider factors affecting teacher's performance," "lack of formative evaluation," "inappropriate data obtained on teacher's performance," "inappropriate feedback providers," "inappropriate feedback recipients," "inappropriate feedback provision," and "no feedback follow-up." Three items of priority involved "inappropriate feedback providers," "inappropriate data," and "failure to consider factors affecting the teacher's performance." CONCLUSIONS: All the raised problems obtained high scores; nevertheless, the interviewees had more problems with the feedback provider, the data collected on the performance, and inattention of university officials to the factors influencing performance than feedback presentation methods. Hence, gaining the trust of teachers on the collected data, providing feedback by their trustworthy individuals, and paying attention to the factors influencing teachers' performance are associated with an increased possibility of feedback acceptance.